2023
DOI: 10.1039/d2cy02015g
|View full text |Cite
|
Sign up to set email alerts
|

Boosting methanol productionviaplasma catalytic CO2hydrogenation over a MnOx/ZrO2catalyst

Abstract: Hydrogenation of carbon dioxide (CO2) to methanol is considered as a potential approach to simultaneously mitigate the global warming and energy crisis issues. As an effective and economic oxide, MnOx...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The CO 2 conversion and methanol yield for plasma only were 5% and 0.0 mg/h, respectively, which was reported in our previous work. [ 19 ] This suggested that the catalyst hardly changed the CO 2 conversion in this plasma catalysis process and it mainly contributed to the formation of methanol. The ZrO 2 alone hardly converted CO 2 to methanol.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CO 2 conversion and methanol yield for plasma only were 5% and 0.0 mg/h, respectively, which was reported in our previous work. [ 19 ] This suggested that the catalyst hardly changed the CO 2 conversion in this plasma catalysis process and it mainly contributed to the formation of methanol. The ZrO 2 alone hardly converted CO 2 to methanol.…”
Section: Resultsmentioning
confidence: 99%
“…They could not be hydrogenated in the plasma catalysis process, which was proved in our previous work. [ 19 ] Their formation could be ascribed to the adsorption of CO 2 by the active oxygen species on the surface of the catalyst. Only (bi)carbonates species were distinguished under the condition without plasma.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations